Ativismo judicial e conflito institucional: análise do caso da prisão após condenação em segunda instância - ASSUNÇÃO, Luís Eduardo Corrêa (2024)
The present study aims to deal with current responses that the political powers of the Union propose to make, in the face of decisions made by the Federal Supreme Court understood by part of the doctrine as being the result of judicial activism, with a special focus on the case of prison after conviction in second instance. The referred case developed over time a certain particularity, namely, the successive capacity, by the STF, to modify its understanding. It is clear, currently, that certain actions of the Supreme Court, especially when related to issues sensitive to society – and this is the case because it is on the list of most important issues for Brazilian society, namely public security –, generate concerns and consequent responses by the Legislative Branch, the Executive or even society, which are called the “backlash effect”, which in turn can ultimately cause a major setback in the field of individual rights, as similar cases demonstrate. This work will be developed using a critical-dialectical approach, through a case study, using the hypothetical deductive method. A bibliographical research will be carried out collecting data obtained from Brazilian legislation, doctrine and jurisprudence.